Forces of nature - Stiefel, Chana, 1968- (Scholastic, 2010)
An exploration of weather that provides information on thunderstorms, earthquakes, blizzards, hurricanes, and other phenomena and offers tips on how to prepare for and stay safe during extreme weather conditions.